Development and characterisation of unsaturated polyester composite incorporating waste rubber glove crumbs as fillers - Mustafa, Nuzaimah (2020)
This thesis, in general, aims to explore the potential of gloves waste rubber to be incorporated into polymer composites and to help minimise waste caused by gloves disposal. This research started with first objective of characterised the rubber crumbs obtained from waste rubber gloves for its shape, size and thermal properties. The waste gloves were downsized into crumbs with size ranging from 300 μm to 2 mm. The crumbs were regular shapes in shape and has smooth surface. The TGA and DSC analyses showed that the degradation pattern of waste gloves crumbs was similar to the degradation pattern of fresh gloves crumbs, suggesting that the properties of waste gloves did not degrade even after they have been disposed of. Second objective of the research was to evaluates the effects of different contents of rubber crumbs on the properties of composites. The rubber crumbs of 5%, 10%, 15%, 20%, 25%, 30%, 35 % and 40 % (by weight) were incorporated into unsaturated polyester. The addition of rubber crumbs has increased the impact strength of the composites by 6% and continues to increase as the content of the rubber increases. This is because the rubber gives a certain degree of elasticity to the composite and has better capacity to absorb energy from the impact load. The addition of crumbs, however, decreased the tensile and flexural strength by 80% and 75% respectively. The strength decreases as the rubber crumbs increase because the adhesion between the crumbs and the polyester becomes weaker due to the agglomeration of the crumbs prevents the polyester from binding well to the rubber surface. Many voids can be seen in the SEM micrographs of the tensile fracture as the content of the crumbs increases in the composite. Third objective was analysed the effect of NaOH, H2S04 and KMnO4 treatment on rubber crumbs surface to the composite’s properties. Composites with NaOH-treated crumbs had improved tensile strength by 2% because NaOH treatment improves the hydrophilicity of the rubber surface, which facilitates better polyester wetting and improves adhesion between rubber and polyester. The rubber crumbs with NaOH treatment have a rougher surface with numerous micropores and microcracks that allow more polyester to penetrate the rubber surface irregularities, thus improving the adhesion of the rubber-polyester. Furthermore, FTIR peak study indicates more polar functional groups and soluble elements on the NaOH-treated rubber surface. These groups initiate further linkages with the polyester polar groups and improves the interfacial adhesion of rubber-polyester. In addition, NaOH eliminated the passive layer created by rubber additives and further reduced the surface contact angle to 31%, allowing for better polyester wetting on rubber. Contrariwise, treatment with H2S04 and KMnO4 decreased the tensile strength of the composites by 2% and 11% respectively. Finally, this research assesses the effect on the properties of composites when crumbs have been treated with different concentrations of sodium hydroxide. The 7% of NaOH treatment concentration on rubber crumbs have sufficiently modified the rubber surface and reduced the contact angle of rubber surface by 27%. It increases the hydrophilicity of the rubber and thus improves the rubber-polyester wettability and adhesion. The 7% NaOH intensively etched the rubber and made the surface rougher, more microcracks and irregularities and eliminating the passive layer on the rubber, thereby creating a greater surface area for polyester coverage and better polyester adhesion. It also induced more functional groups as FTIR revealed higher peak intensities, which generate more linkages with polar groups in polyester. These factors strengthened the interfacial rubber-polyester adhesion as the SEM micrograph tensile fracture showed that the rubber crumbs remained intact in the polyester matrix after fractured. In conclusion, waste rubber gloves can be incorporated into unsaturated polyester composites as it improves the composites toughness. Treatment of rubber crumbs with a concentration of 7% of NaOH has effectively modified the rubber surface and strengthens the adhesion between rubber and polyester resulting in improved composite properties.